Between Dixie and Zion : Southern Baptists and Palestine before Israel - Robins, Walker, 1987- (Religion and American culture (Tuscaloosa, Ala.), 2020)
"This work explores the roots of evangelical Christian support for Israel through an examination of the largest Protestant denomination in the United States, the Southern Baptist Convention, in the decades leading up to the establishment of the Jewish state in 1948. One week after the establishment of the State of Israel in 1948, delegates to the Southern Baptist Convention (SBC) repeatedly and overwhelmingly voted down resolutions congratulating fellow Southern Baptist Harry Truman on his role in Israel's creation. From today's perspective, this seems a shocking result. After all, Christians--particularly the white evangelical Protestants that populate the SBC--are now the largest pro-Israel constituency in a US population that is very supportive of the Jewish state generally. How could conservative evangelicals have been so hesitant in celebrating Israel's birth in 1948? How did they then come to be so supportive? 'Between Dixie and Zion: Southern Baptists' Palestine Questions' addresses these issues by offering a comprehensive look at Southern Baptist engagement with what was called the 'Palestine question'--the question of whether Jews or Arabs would, or should, control the Holy Land after World War I. Walker Robins argues that, in the decades leading up to the creation of Israel, most Southern Baptists did not directly engage the Palestine question as a political question. Rather, they engaged it indirectly through a variety of encounters with the land, the peoples, and the politics of Palestine, among them tourists, foreign missionaries, native Arabs, Jewish converts, Biblical interpreters, fundamentalist rebels, editorialists, and, of course, even a president. While all revered Palestine as the Holy Land, each had their own priorities in approaching the region that were shaped by the ways in which they encountered it. Each, in other words, had their own 'Palestine questions.' Between Dixie and Zion shows that Baptists consistently looked at the region with orientalist eyes, broadly associating the Zionist movement with Western civilization, modernity, and progress over and against the Arabs, whom they viewed as uncivilized, pre-modern, and backward. It argues that such impressions were not idle--they suggested that the Zionists were fulfilling Baptists' long-expressed hopes that the Holy Land would one day be revived and regain the prosperity it had held in the biblical era"--